Factors influencing the online buying behaviour of the consumer: A case study on students of Marien Ngouabi University - Ngongo, Nevie Chrislie Kinzonzi; Amoateng, Priscilla Achiaa (Technium Social Sciences Journal, 2022)
The Republic of Congo is gaining importance as a lucrative market for traders. Since the recent economic revolution, Congolese consumers have recently begun understanding the benefits of using the internet to shop. However, a growing number of internet users have not been reflected in online sales. Therefore, it is important to identify the factors that affect the Republic of Congo in its bid for online shoppers to find a way to promote their online shopping behaviour. The purpose of this study was to identify factors that affect the perception of Republic of Congo consumers about online shopping by investigating Congolese consumer perceptions about online shopping. The tested factors include pre-identified features (Market Motivation, Psychological, personal and social) and specific factors in Congo (Social, Cost, and brand) for this study. The findings suggest that cost and product brand are important factors that influence the consumer’s behaviour when shopping online.